Protocol for live imaging of intracellular nanoscale structures using atomic force microscopy with nanoneedle probes - Ichikawa, Takehiko; Alam, Mohammad Shahidul; Penedo, Marcos; Matsumoto, Kyosuke; Fujita, Sou; Miyazawa, Keisuke; Furusho, Hirotoshi; Miyata, Kazuki; Nakamura, Chikashi; Fukuma, Takeshi (STAR protocols, 2023)
Atomic force microscopy (AFM) is capable of nanoscale imaging but has so far only been used on cell surfaces when applied to a living cell. Here, we describe a step-by-step protocol for nanoendoscopy-AFM, which enables the imaging of nanoscale structures inside living cells. The protocol consists of cell staining, fabrication of the nanoneedle probes, observation inside living cells using 2D and 3D nanoendoscopy-AFM, and visualization of the 3D data. For complete details on the use and execution of this protocol, please refer to Penedo et al. (2021)1 and Penedo et al. (2021).2 [Display omitted] •Fabrication of nanoneedle tip by EBD or FIB-milling•Step-by-step guide for 2D and 3D nanoendoscopy-AFM imaging•Visualization of 3D intracellular structures from 3D nanoendoscopy-AFM data Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. Atomic force microscopy (AFM) is capable of nanoscale imaging but has so far only been used on cell surfaces when applied to a living cell. Here, we describe a step-by-step protocol for nanoendoscopy-AFM, which enables the imaging of nanoscale structures inside living cells. The protocol consists of cell staining, fabrication of the nanoneedle probes, observation inside living cells using 2D and 3D nanoendoscopy-AFM, and visualization of the 3D data.